Legal Protection of Ownership of Hospital Land Rights Following the Issuance of Regulation of the Minister of Health of the Republic of Indonesia Number 56 of 2014 Concerning Classification and Licensing of Hospitals - Susiawanto, Djarot Egro (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The problem of hospital land ownership status began when the Minister of Health Regulation Number 56 of 2014 was issued, based on article 1 of PERMENKES Number 56 of 2014, namely